HUBUNGAN GAYA KEPEMIMPINAN, POLA KOMUNIKASI, DAN KEPUASAN KERJA DENGAN PRODUKTIVITAS KARYAWAN - Alya Anwar, Rizqika; Pradekso, Tandiyo; Suryanto Gono, Joyo Nur (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research is motivated by data from the Ministry of Manpower in 2022, showing that employee productivity in Central Java is low compared to other provinces in Indonesia, where Central Java ranks 27 out of 34 provinces. The district in Central Java that has a lower level of employee productivity compared to other districts is Jepara Regency. The research method used is explanatory quantitative research with a total sample of 100 respondents who are employees in Jepara Regency, aged 17-56 years, and have more than 1 year of work experience. The data collected were analyzed using two techniques, namely the Chi Square and Kendall's Tau B tests. The results showed that there was no relationship between leadership style and employee productivity (significance value 0.091). However, there is a relationship between communication patterns and employee productivity (significance value 0.04). In addition, there is a relationship between job satisfaction and employee productivity (significance value 0.00).